The Development and Correlates of Gender Role Orientations in African‐American Youth. Issue 5 (5th May 2017) - Skinner, Olivenne D.; McHale, Susan M.
Abstract : This study charted the development of gendered personality qualities, activity interests, and attitudes across adolescence (approximately ages 9–18) among 319 African‐American youth from 166 families. The relations between daily time spent with father, mother, and male and female peers—the gendered contexts of youth's daily activities—and (changes in) these gender role orientations were also assessed. Boys and girls differed in their gender role orientations in stereotypical ways: interest in masculine and feminine activities, and attitude traditionality generally declined, but instrumentality increased across adolescence and expressivity first increased and later decreased. Some gender differences and variations in change were conditioned by time spent with same‐ and other‐sex gender parents and peers. The most consistent pattern was time with male peers predicting boys' stereotypical characteristics.